IACSC 2016 FOCUSES ON PROSPEROUS URBAN LIVING IN THE 21ST CENTURY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 6 September 2016 The UNHabitat’s State of the World Cities 2012/2013 Reported Prosperity of Cities specifically highlighted that the five pillars of a prosperous city are economic productivity; infrastructure development; quality of life; equity and social inclusion; and environmental sustainability.